What knowledge management approach do entrepreneurial universities need?. (November 2019) - Calvo, Nuria; Rodeiro-Pazos, David; Rodríguez-Gulías, María Jesús; Fernández-López, Sara
Abstract: This paper explores how universities' entrepreneurial outcomes (patents, university spin-offs, research projects and R&D contracts) relate to the availability and use of information and telecommunications (IT) solutions for knowledge management (KM), looking at the period 2011–2014. We hypothesized that entrepreneurial universities may benefit from a good connection between knowledge infrastructure (IT solutions) and KM processes. We tested this hypothesis by estimating generalized least squares models and negative binomial regression models for a sample of 63 Spanish universities over the period 2011–2014. The results show that using a data grouping infrastructure improves several measures of entrepreneurial outcomes of universities. Unexpectedly, institutional tools for collaborative working and data warehouses significantly decrease the number of patents. From these results, we suggest that process-oriented approaches for KM may worsen the entrepreneurial outcomes of universities. The contribution of this analysis is twofold. First, it gives a better empirical understanding of the way in which IT solutions for KM affect universities' entrepreneurial outcomes. Second, this analysis could guide a new design for IT solutions in order to improve these outcomes. Highlights: Entrepreneurial universities connect IT solutions and KM processes. Data grouping infrastructure increases some entrepreneurial outcomes of universities. Process-oriented KM results in some entrepreneurial outcomes.